The Effectiveness Of The Accelerated Learning Model In Increasing Student Learning Motivation - Mharchelya; Neviyarni S (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Students often have difficulty completing tasks during the learning process. They believe learning is difficult, unpleasant and boring. Increased complexity means that better methods of learning are needed to get students to participate in the learning process in the classroom, so that those who feel bored with the lesson will be able to understand it more quickly. This condition often occurs because students pay less attention to the teacher during the learning process and do not do the teacher's assignments directly. Accelerated Learning is a natural learning method. The Accelerated Learning approach is a learning method that aims to improve students' ability to understand and apply the lessons taught by the teacher in a way that is interesting and not boring for students. This approach naturally fosters students' drive to learn more actively and more. Accelerated learning prioritizes results over methods or processes. This approach is usually flexible, exhilarating, has many options, emphasizes cooperation, and is multi-sensory. One of the learning methods that can be used to achieve learning objectives is accelerated learning. This article uses a descriptive qualitative approach with library research using books, manuscripts, articles, and other documentation.